Light‐controllable polymeric material based on temperature‐sensitive hydrogels with incorporated graphene oxide. Issue 6 (24th March 2015) - Breuer, L.; Raue, M.; Kirschbaum, M.; Mang, T.; Schöning, M. J.; Thoelen, R.; Wagner, T.
Abstract Poly(N‐isopropylacrylamide) (PNIPAAm) hydrogel films with incorporated graphene oxide (GO) were developed and tested as light‐stimulated actuators. GO dispersions were synthesized via Hummers method and characterized toward their optical properties and photothermal energy conversion. The hydrogels were prepared by means of photopolymerization. In addition, the influence of GO within the hydrogel network on the lower critical solution temperature (LCST) was investigated by differential scanning calorimetry (DSC). The optical absorbance and the response to illumination were determined as a function of GO concentration for thin hydrogel films. A proof of principle for the stimulation with light was performed.